Nanoemulsões do extrato do cálice de Physalis peruviana: desenvolvimento, avaliação da estabilidade e estudos de toxicidade - Bazana, Maiara Taís (2019)
Physalis peruviana presents a variety of biologically active compounds, especially in its calyx, which is considered a byproduct with potential to be explored and reused. Among the most promising technologies in the food industry, nanotechnology stands out with its ability to encapsulate various compounds, which have limitations. However, this technology still requires further studies on the nanotoxicity of formulations and its use in waste generated by industries. Therefore, the objective of this study was to develop nanoemulsions containing the P. peruviana calyx extract and evaluate the stability of the extract and nanoemulsions against different storage conditions, antioxidant capacity, and in vitro and in vivo toxicity, aiming its application in food. The extracts were prepared in 60% ethanol and characterized by antioxidant capacity, reducing capacity, HPLC-quantified major compound, antibacterial activity, and antibiofilm capacity. Nanoemulsions were prepared by the spontaneous emulsification method and physically and chemically characterized. Afterwards, the stability of the extracts and nanoemulsions were evaluated under different storage conditions, such as temperatures of 7 and 25 °C with the absence or incidence of light for 120 days. Additionally, the release of the major compound from the nanoemulsions and extract in a simulated gastrointestinal environment, the in vitro toxicity in tumor cell lines (MCF-7 breast cancer) and non-tumor cell lines (3T3 fibroblasts), and in vivo (using the Caenorhabditis elegans model) were evaluated. The P. peruviana calyx extract was characterized by its reducing capacity (610 mg Eq. of gallic acid/100 g of calyx), antioxidant capacity (138 μmol Trolox/g of calyx), and rutin content (11.3 μg/mL). The minimum inhibitory concentration ranged from 3.15 to 30 mg/mL extract, showing bacteriostatic activity against eight pathogens and bactericidal activity at 30 mg/mL concentration against six strains. Nevertheless, the extract inhibited the formation of biofilm produced by Pseudomonas aeruginosa PA01, although there was no destruction. The nanoemulsions had nanometric droplet size (160-180 nm), polydispersity index below 0.15, zeta potential (-8 to -11 mV), slightly acidic pH (5.4 to 6.3), droplets (unimodal peak in the nanometer range), morphology (spherical shape and smooth surface), rutin content (11 μg/mL), and encapsulation efficiency of 85%. Among the tested samples, the highest stability was observed in nanoemulsions containing the P. peruviana calyx extract when stored at room temperature and in the absence of light. The extract and nanoemulsions of the extract showed no toxicity in the non-tumor cell line. However, as the concentration of nanoemulsions increased, they demonstrated cytotoxicity against the tumor cell line. In the in vivo model, all samples analyzed did not cause toxicity to C. elegans in the survival test. Regarding resistance to oxidative stress, the formulations exerted their antioxidant effects at low concentrations in vivo. In addition, the rutin present in the nanoemulsion extract showed greater stability against the degradation of simulated gastrointestinal conditions compared to the free extract, controlling the release and increasing the levels of bioactive compounds released in the duodenum and ileum, which is where absorption occurs. Therefore, this study contributes to future applications in the food area to be studied and deepened.